2018
DOI: 10.1002/berj.3443
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of lesbian, gay and bisexual students and staff at a Further Education college in South East England

Abstract: Research exploring the educational experiences of lesbian, gay and bisexual (LGB) students and staff members has traditionally been characterised by homophobia, hostility, victimisation and marginalisation. Recent research has evidenced a shift in the experiences of LGB young people, to somewhat more accepting and positive narratives, including within post-compulsory schooling. Yet, there is limited research exploring the lived experiences of LGB staff members in the Further Education context. Utilising inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
1
10
2
1
Order By: Relevance
“…The study found that within these TGD youth, rates of bullying were very high, with the majority reporting having experienced bullying (86.5%), with name calling being extremely common (reported by 96% of the bullied participants). This is somewhat higher than many recently reported rates of bullying in the general population (22% in 12-20-year olds 55 ) and in LGB youth (55% in 2012, and 65% in 2007 44,56 ), suggesting that TGD youth are at increased risk for bullying compared with sexual minority youth. It is also higher than in the most recent Stonewall reports of transgender youth (64% in 2017 44 ), which may reflect differences in the experiences of youth who have already accessed health care.…”
Section: Discussioncontrasting
confidence: 54%
“…The study found that within these TGD youth, rates of bullying were very high, with the majority reporting having experienced bullying (86.5%), with name calling being extremely common (reported by 96% of the bullied participants). This is somewhat higher than many recently reported rates of bullying in the general population (22% in 12-20-year olds 55 ) and in LGB youth (55% in 2012, and 65% in 2007 44,56 ), suggesting that TGD youth are at increased risk for bullying compared with sexual minority youth. It is also higher than in the most recent Stonewall reports of transgender youth (64% in 2017 44 ), which may reflect differences in the experiences of youth who have already accessed health care.…”
Section: Discussioncontrasting
confidence: 54%
“…Many students however did acknowledge that the situation was improving, somewhat in line with Stonewall (2017) findings; this was largely due to the efforts of individual teachers and the development of support groups (with the caveats noted earlier). The data presented here does not, however, support the view found in some research (e.g., McCormack and Anderson 2010;White, Magrath, and Thomas 2018), which argues there has been a significant shift in attitudes and that homophobia, rather than homosexuality, was stigmatised. The issue may be that these studies have focused more specifically on the experience of homosexual and bisexual males; seemingly these are currently 'more acceptable' ways of being LGBT+.…”
Section: Disconnect Between Student Experiences and The Views That Teachers Have Of Thesecontrasting
confidence: 99%
“…During the 1980s and 1990s, UK government policy helped to create a generally hostile environment for the LGBT+ community (see White, Magrath, and Thomas 2018). This resulted in many schools avoiding any discussion about issues of sexuality (Epstein 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the inclusion of marginalised groups in education are numerous, particularly in the area of pre-tertiary education. The following marginalised groups are discussed: children with special education needs (SEN) (Shaw, 2017), race and ethnic minorities (Curcic et al, 2014), immigrants (Cropley, 2017), religious minorities (Mirza and Meetoo, 2018), girls, particularly in developing countries, (Harper et al, 2018), the LGBTQIA community (lesbian, gay, bisexual, trans-gender/sexual, queer, intersex and asexual people) (White et al, 2018) and children from lower socio-economic backgrounds (Riessman and Miller, 2017).…”
Section: Neoliberalism and Inclusion: Conflicting Or Mutually Constitmentioning
confidence: 99%